2005
DOI: 10.1079/bjn20051574
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits are major determinants of the plasma antioxidant status in healthy elderly subjects

Abstract: Previous studies indicate that regular consumption of a diet rich in fruits and vegetables is associated with a lower risk for age-related diseases. The aim of the present study was to evaluate whether the often-reported age-related decrease of plasma antioxidants in man depends on differences in dietary intake or on other age-and gender-related factors. In this observational case-control study, thirty-nine community-dwelling healthy subjects aged 65 years and older consuming high intakes of fruits and vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 27 publications
2
39
0
3
Order By: Relevance
“…85 A study has shown that greater ingestion of fruits and vegetables is associated with lower lipid peroxidation, as well as a higher plasmatic concentration of lipophilic antioxidants (β-carotene, α-tocopherol and lycopene). 86 Recent work has verified the positive associated between consumption of foods rich in antioxidant substances and plasmatic levels of α-tocopherol, vitamin C and total antioxidant activity. 87 On the other hand, a positive correlation was not verified between the ingestion of foods that are a source of β-carotene and plasmatic levels of this antioxidant in elderly residents of a community in Ireland.…”
Section: Nutritional Status and Oxidative Stressmentioning
confidence: 99%
“…85 A study has shown that greater ingestion of fruits and vegetables is associated with lower lipid peroxidation, as well as a higher plasmatic concentration of lipophilic antioxidants (β-carotene, α-tocopherol and lycopene). 86 Recent work has verified the positive associated between consumption of foods rich in antioxidant substances and plasmatic levels of α-tocopherol, vitamin C and total antioxidant activity. 87 On the other hand, a positive correlation was not verified between the ingestion of foods that are a source of β-carotene and plasmatic levels of this antioxidant in elderly residents of a community in Ireland.…”
Section: Nutritional Status and Oxidative Stressmentioning
confidence: 99%
“…In this study, lycopene, a powerful antioxidant carotenoid, was associated with several measures of cognitive performance. Previous studies showed that levels of circulating carotenoids, among other micronutrients, are associated with fruit and vegetable intake in the healthy elderly (Anlasik et al 2005). In addition, plasma levels of carotenoids and other micronutrients might be increased through a nutritional interventional program with high intakes of fruits and vegetables (Polidori et al 2009b).…”
Section: Why Should We Care About Diet and Nutrition Against Cognitivmentioning
confidence: 99%
“…22,23 Four cohort studies have been conducted in the past decade that collectively suggest an inverse relation between risk of MaND and vegetable and fruit consumption. [24][25][26][27] According to the National Institutes of Health, the Three-City Cohort Study 28 showed a risk reduction in MaND by about 30% in daily consumers of fruits and vegetables compared with subjects rarely consuming fruits and vegetables. In the Esprit study, consumption of fewer than 2 portions of fruits and vegetables per day was associated with a significantly higher risk of MiND and MaND compared with subjects consuming more than 2 portions.…”
Section: Diet and Nutritionmentioning
confidence: 99%